Improving support for children with autism and their families using a 100 day challenge framework. (30th November 2021) - Wallace-Thompson, Lauren; Rose, Jason
Abstract : Community-based support for autistic children and their families can prevent individuals from reaching crisis point and reduce inpatient admissions.1 Lauren Wallace-Thompson and Jason Rose describe how they set up a joint initiative with Bromley Council and the parents and carers of children and young people with autism, and what changes this has introduced.